Solve for y -4=8y-9y+6

Math
-4=8y-9y+6
Rewrite the equation as 8y-9y+6=-4.
8y-9y+6=-4
Subtract 9y from 8y.
-y+6=-4
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 6 from both sides of the equation.
-y=-4-6
Subtract 6 from -4.
-y=-10
-y=-10
Multiply each term in -y=-10 by -1
Tap for more steps…
Multiply each term in -y=-10 by -1.
(-y)⋅-1=(-10)⋅-1
Multiply (-y)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1y=(-10)⋅-1
Multiply y by 1.
y=(-10)⋅-1
y=(-10)⋅-1
Multiply -10 by -1.
y=10
y=10
Solve for y -4=8y-9y+6

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top